2021
DOI: 10.1002/app.50865
|View full text |Cite
|
Sign up to set email alerts
|

Tuning piezoelectric properties in elastomeric polyurethane nanocomposites utilizing cellulose nanocrystals

Abstract: Flexible piezoelectric nanocomposites have been the subject of a lot of recent research due to the development and use of wearable electronic devices and the increasing need for new harvesting devices and sensors due to increasingly intelligent and interconnected cities. In this study, flexible piezoelectric nanocomposites using elastomeric polyurethane (PU) as matrix, and lead zirconate titanate (PZT) as active phase, were produced using cellulose nanocrystals (CNC) as the third phase. The study describes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…It can be observed that PZT has little influence on the σ dc values of the PUR/PZT piezoelectric composite. This small increase in σ dc can be attributed to the ionic and electronic conduction processes that occur preferentially in PZT grains 42,43 . On the other hand, MWCNT impacted on the σ dc value of three‐phase PUR‐MWCNT/PZT piezoelectric composite.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…It can be observed that PZT has little influence on the σ dc values of the PUR/PZT piezoelectric composite. This small increase in σ dc can be attributed to the ionic and electronic conduction processes that occur preferentially in PZT grains 42,43 . On the other hand, MWCNT impacted on the σ dc value of three‐phase PUR‐MWCNT/PZT piezoelectric composite.…”
Section: Resultsmentioning
confidence: 96%
“…The stronger decrease in σ dc value to piezoelectric composite containing 3 wt.% MWCNT (PUR‐MWCNT3/PZT), when PZT concentration increased, can be related to barrier effects that arise by breaking the connectivity of the percolative conduction pathway formed by MWCNT 44 . For high PZT fractions, free volume is reduced in the matrix, therefore constraining MWCNT to minute polymeric regions and facilitating their interaction through van der Waals bonds, which results in aggregation 43 . The increase in PZT concentration also increases the energy barrier that charge carriers must overcome to flow through a material when an electric field is imposed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely acknowledged that to boost the piezoelectric performance of pure piezoelectric materials, incorporating other components to construct hybrid systems demonstrates a powerful approach to make up for the shortcomings of each component and to exploit synergy effects [ 109 , 110 , 111 , 112 , 113 , 114 ]. Baur et al [ 109 ] enhanced the piezoelectric performance of PVDF with carbon fluoropolymer nanocomposites.…”
Section: The High-temperature Piezoelectric Materialsmentioning
confidence: 99%